Systematic review of descriptive cohort studies on the dynamics of glycaemia among adults admitted to hospital with acute stroke. (13th July 2012) - Laird, Elizabeth A.; Coates, Vivien; Chaney, David
Abstract Aim This article presents the results of a systematic review of descriptive cohort studies on the dynamics of glycaemia among adults admitted to hospital with acute stroke. Background Hyperglycaemia is common among adults admitted to hospital with stroke. Design Systematic review. Data sources A search for descriptive cohort studies published between January 1996–June 2011, was conducted in MEDLINE, PubMed and Embase electronic databases. The search was performed using the terms 'stroke', 'hyperglycaemia' and/or 'glucose' combined and limited to adults and English language publications. Searching of citations from identified studies supplemented the electronic searches. Review methods A systematic review was conducted of eight studies, meeting the criteria of: (1) descriptive cohort studies; (2) adults admitted to hospital with acute stroke; and (3) glycaemic status monitored over at least two consecutive days from admission to hospital. The review adheres to the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis standards. Results The dynamics of glycaemia after stroke has been investigated in seven prospective cohort studies and one retrospective study. The patterns that emerged were persisting normoglycaemia, transient hyperglycaemia, persisting hyperglycaemia and delayed hyperglycaemia. Surges in glycaemia are likely on days 2 and 3 and some adults will not exhibit hyperglycaemia till day 7. Conclusion Further large cohort studies are required to explore the dynamic of glycaemia after stroke for at least 1 week duration. The timing of formal screening for diabetes mellitus is important, as early screening may overestimate detection rates.